2017
DOI: 10.1016/j.jedc.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Disaster risk and preference shifts in a New Keynesian model

Abstract: This paper analyzes the effects of a change in a small but timevarying "disaster risk" à la Gourio (2012) in a New Keynesian model. In a real business cycle framework, the disaster risk has been successful in replicating observed moments of equity premia. However, responses of macroeconomic variables critically depend on the value of the elasticity of intertemporal substitution (EIS). In particular, we show here that an increase in the probability of disaster causes a recession only in case of an EIS larger th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…Third and most importantly, empirical evidence is sufficiently important for some of the model parameters required in the theoretical simulation exercises presented here. In particular, the elasticity of intertemporal substitution and the degree of price stickiness play a key role in the responses, as explained in Isoré and Szczerbowicz (2017). These parameters are well documented for this group of countries, unlike for example South-Asian countries of similar income levels (see Subsection 4.1).…”
Section: Evidence On Natural Disasters In Latin Americamentioning
confidence: 86%
See 4 more Smart Citations
“…Third and most importantly, empirical evidence is sufficiently important for some of the model parameters required in the theoretical simulation exercises presented here. In particular, the elasticity of intertemporal substitution and the degree of price stickiness play a key role in the responses, as explained in Isoré and Szczerbowicz (2017). These parameters are well documented for this group of countries, unlike for example South-Asian countries of similar income levels (see Subsection 4.1).…”
Section: Evidence On Natural Disasters In Latin Americamentioning
confidence: 86%
“…Gabaix (2011), Gabaix (2012), and Gourio (2012) have introduced a small but time-varying probability of disasters in real business cycle models, and find that changes in the probability of disasters, without any arrival of the disaster itself, may suffice to trigger economic recessions. Isoré and Szczerbowicz (2017) further showed how to extend this approach to a New Keynesian environment, and found that disaster risk shocksn-again, absent of actual disaster realization-, generate procyclical responses of consumption, investment, labor, wage, and inflation, simultaneously to the recession and rise in equity premium. Further empirical evidence by Siriwardane (2015) and Marfè and Penasse (2017) support the relationship between changes in the probability of a disaster and macroeconomic variables.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations